Adherence to highly active antiretroviral treatment and loss to follow-up of pregnent women at the Themba Lethu Clinicu - Nagar, Shashikala (My University, 2011)
INTRODUCTION Although much focus has been placed towards rapid scale-up of antiretroviral treatment programmes and interventions for the prevention of mother-to-child transmission of human immunodeficiency virus (HIV), very little is known about adherence to highly active antiretroviral therapy (HAART) and loss to follow-up of pregnant women in antiretroviral treatment programmes in the developing world. In this retrospective cohort analysis, we described the baseline characteristics of adult women who were pregnant at the time of HAART initiation (pregnant at start) as well as women who became pregnant during follow-up after starting HAART (pregnant after) and women who never had a pregnancy (not pregnant) during the study period. We evaluated the association of pregnancy status with adherence and loss to follow-up in these three groups of women. MATERIALS AND METHODS Themba Lethu Clinic is an urban public-sector antiretroviral rollout facility in Johannesburg, South Africa. A retrospective analysis was conducted of all adult women initiating HAART at this clinic between January 2005 and December 2007. Clinical data from these patients was analysed for differences in rates of loss to follow-up, and measured adherence rates based on CD4 cell count response and virologic suppression. Regression models were performed to determine independent predictors of adherence and loss to follow-up and compared between the three groups. Survival analysis, in the form of Kaplan-Meier plots and log-rank tests, was used to compare the time to becoming lost to follow up. RESULTS Between 1 January 2005 and 31 December 2007, 5129 women initiated HAART at Themba Lethu Clinic, Johannesburg, South Africa. Of these women, 521 (10.0%) were pregnant at the time of HAART initiation (pregnant at start) and 291 (5.6%) became pregnant during follow-up (pregnant after). Women who were pregnant at start (16.6%) of HAART had less-advanced HIV disease than the not pregnant women and pregnant women after HAART initiation 4608 (89.9%). Overall pregnant women were significantly younger than the not pregnant women and fewer pregnant women had a CD4 <100 cells/mm3 and a WHO stage III of HIV disease. There was no significant difference in the CD4 cell count response and virological suppression between the three groups of women based on pregnancy status at 6 months and 12 months (X2=2.1, p=0.347 and X2=4.4, p=0.111 respectively). However, women pregnant at start were more likely to become lost to follow-up (X2=15.8, P=<.0001) during follow up. In the multivariate Cox logistic regression model, independent predictors of loss to follow-up were pregnancy, baseline CD4 cell count and age at initiation. Being pregnant was significantly associated with being loss to follow-up. CONCLUSIONS Pregnancy is significantly associated with defaulting treatment and becoming lost to follow-up from HAART treatment programmes. Together with being pregnant, young age and a low CD4 at baseline are high risk factors for non adherence and loss to follow-up in this sub-group of the population. Early initiation of HAART with adequate pre-treatment counselling and ongoing adherence support could help improve adherence and retention in care for patients in treatment programmes in resource-limited settings. Interventions to trace patients immediately upon missed appointments would help to reduce the number of patients’ loss to follow-up. Moreover, integration of tuberculosis (TB), antenatal care (ANC) and HIV treatment services may maximize the effectiveness of interventions aimed at reducing the loss to follow-up rate. The initiation of HAART in pregnancy requires strengthened antenatal and HIV services that target women with advanced stage disease.
MPH, School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, 2010
Keywords: antiretroviral treatment; pregnant women; adherence; follow-up; HAART